Governing the Second Quantum Revolution: An Adaptive Public Administration Framework for Responsible Quantum Technologies - Emely Wiegand (SWATANTRA, 2025)
Quantum technologies are increasingly moving from specialist laboratories into the strategic agenda of governments, industries, and international organisations. Quantum computing, quantum communication, and quantum sensing are expected to reshape cybersecurity, scientific discovery, industrial productivity, public infrastructure, and national competitiveness. Yet the same technologies also raise complex governance challenges, including cryptographic vulnerability, dual-use risks, technological inequality, workforce shortages, procurement uncertainty, and the concentration of innovation capacity in a small number of advanced economies. This article develops an adaptive public administration framework for responsible quantum technology governance. Using qualitative document-based policy analysis, the study examines international policy documents, responsible innovation literature, quantum technology roadmaps, post-quantum cryptography guidance, and emerging governance principles. The article argues that quantum technologies should not be governed only as technical artefacts or national security assets, but also as public policy objects whose societal consequences require anticipatory, inclusive, and institutionally coordinated governance. The proposed Quantum Public Administration Governance Framework consists of five interrelated dimensions: foresight and anticipatory intelligence, cybersecurity and cryptographic readiness, institutional coordination, responsible innovation and public value, and equity-oriented capacity building. The findings suggest that public administrations need to build quantum literacy, establish cross-sector coordination mechanisms, prepare digital infrastructure for post-quantum risks, support ethical and socially beneficial innovation, and prevent the emergence of a global and domestic quantum divide. The article contributes to public administration scholarship by translating the technical uncertainty of quantum technologies into a governance agenda that is relevant for policy makers, public managers, and emerging economies seeking to participate responsibly in the second quantum revolution.